Konsep Makanan Halal dalam Tinjauan Syariah dan Tanggung Jawab Produk Atas Produsen Industri Halal - Muchtar Ali (AHKAM : Jurnal Ilmu Syariah, 2016)
The Concept of Halal Food in Sharia Perspective and Product Responsibility of Halal Industry. Sharia provisions regarding halal and haram food, beverages, and goods are integral parts of Islamic teachings. Halal and haram foods also have become a necessity related to the comfort and safety of the Muslims as the largest consumers in Indonesia. This need should be enforced by halal industry. Every manufacturer of halal foods should have an understanding and awareness to ensure their halal products by implementing a Halal Assurance System as the implementation of sharia concept of halal and haram on food and drinks. The violation of Halal Assurance System by the manufacturer will be subject to product liability, both legally and morally.DOI: 10.15408/ajis.v16i2.4459